2023
DOI: 10.3389/fmed.2023.992493
|View full text |Cite
|
Sign up to set email alerts
|

Does pronator quadratus repair affect functional outcome following volar plate fixation of distal radius fractures? A systematic review and meta-analysis

Abstract: IntroductionThe study aimed to evaluate the efficacy of pronator quadratus (PQ) repair versus no repair following volar plate fixation of distal radius fractures.MethodsA comprehensive search was performed in PubMed, CNKI, EMBASE, Web of Science, Ovid, and Cochrane Library databases. All randomized controlled trials comparing PQ repair with no repair in distal radius fractures before January 2023 were included. Two investigators independently screened eligible articles, assessed the study quality, and extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, they did not assess the contribution of the two PQ heads separately. The systematic review and metaanalysis carried out by Ying et al (2023) showed that PQ repair may increase grip strength and pronation function in the short-term. However, owing to the limited number of studies included in that review (n ¼ 7), more data from larger studies are needed to verify those conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did not assess the contribution of the two PQ heads separately. The systematic review and metaanalysis carried out by Ying et al (2023) showed that PQ repair may increase grip strength and pronation function in the short-term. However, owing to the limited number of studies included in that review (n ¼ 7), more data from larger studies are needed to verify those conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not assess the contribution of the two PQ heads separately. The systematic review and meta-analysis carried out by Ying et al. (2023) showed that PQ repair may increase grip strength and pronation function in the short-term.…”
Section: Discussionmentioning
confidence: 99%
“…Distal radial fracture is the conjuncture of cancellous and cortical bone, which is a fracture within 3 cm of the distal radius articular surface [ 1 3 ]. The incidence of osteoporosis, which easily leads to high loss and fracture fragment comminution after injury, accounts for about 17% of emergency orthopedic patients [ 4 ], and the data will improve as our population ages.…”
Section: Introductionmentioning
confidence: 99%